Planning and Timing in Inland Navigation - Horváth, G. (Acta Technica Jaurinensis, 2011)
Hungary has a central position considering both geographical position and waterway networks, so changes in the inland waterway transport tendencies can be obviously experienced. In Middle-Europe the traffic outputs don’t reflect the theories of conception on sustainable transport. The dividend of inland navigation from total modal split is insufficient. What are the reasons of the state of being slighted? How can be enforced the well-known ecological and economical advantages of shipping? It is important to gauge the specialities of river transport planning. Due to transformation of shipping market and disproportional module differences, forecasts are strongly focused on. Beside network development, infrastructural modernising and a suitable charging policy it is important to improve reliability if you wish to take the advantages of waterway transportation. As a basis for this you need an appropriate transportation planning system.